2020
DOI: 10.3390/app10228080
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Electric Propulsion System Model for Performance Analysis of Large-Size Multicopter UAVs

Abstract: In this study, an improved model of the electric propulsion system is proposed in order to analyze the performance of large-size multicopter unmanned aerial vehicles. The main improvement of the proposed model is to reflect the armature reaction of the motor, which effectively explains the significant performance degradation in high-power operation. The armature reaction is a phenomenon, in which the main field flux is interfered by a magnetic flux and, as the size and output of the motor increase, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The model proposed in this study includes various mathematical models for propellers, motors, electric speed controllers and batteries, which are key components of the electric propulsion system and can calculate key performance data such as thrust and torque and power consumption. It confirmed that the proposed model can predict performance in high-power operation of electric propulsion systems for large multirotor platforms, although some errors were noted (Jeong et al , 2020; Magnussen et al , 2015). Vu et al (2019) and Dai et al (2019) propose a practical method to help them quickly select the optimum products of the propulsion system to maximize multirotor efficiency under desired flight conditions.…”
Section: Introductionsupporting
confidence: 64%
“…The model proposed in this study includes various mathematical models for propellers, motors, electric speed controllers and batteries, which are key components of the electric propulsion system and can calculate key performance data such as thrust and torque and power consumption. It confirmed that the proposed model can predict performance in high-power operation of electric propulsion systems for large multirotor platforms, although some errors were noted (Jeong et al , 2020; Magnussen et al , 2015). Vu et al (2019) and Dai et al (2019) propose a practical method to help them quickly select the optimum products of the propulsion system to maximize multirotor efficiency under desired flight conditions.…”
Section: Introductionsupporting
confidence: 64%
“…In research aimed at testing the performance of large-scale tandem UAVs [27], electric propulsion units (EPUs) consisting of a 28*8.4" propeller and U8 100 Kv motor were experimentally tested. An improved model of the electric propulsion system was presented in [28], where three EPU setups were experimentally tested. This research focuses on the armature reaction of the motor, effectively explaining the significant performance degradation during high-power operation.…”
Section: Introductionmentioning
confidence: 99%